Treatment and prevention of the recurrence of liver echinococcosis - R. T. Mejidov; R. S. Sultanova (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to make the comparative assessment of surgical methods for the treatment and prevention of the recurrence of echinococcal liver disease, as well as to study negative and positive aspects of closed echinococcectomy in relation to recurrent efficacy.METHODS AND MATERIAL. 1072 cases (1358 cysts) of echinococcal liver disease were subjected to a retrospective analysis. The clinic performed radical (closed) echinococcectomy using high-tech resection devices on 258 patients, including ultrasound dissectors and destructors-aspirators for 105 patients (main group), other resection devices (LigaSure, an argon plasma scalpel) for patients (control group).RESULTS. Inpatient treatment of patients in the main group amounted to (9.4±2.1) days, in the control group – (11.6±1.7). Postoperative complications in the main group were observed at 4.6 % of patients, in the control group – 11.0 %. Relapse of the liver echinococcosis in the control group occurred in 2.3 % of cases, there were no relapses in the main group. The quality of life of patients in the main group was (73.5±1.8) points, in the control group – (72, 8±1.7) points. There were no lethal outcomes in both groups of patients.CONCLUSION. The most effective in the treatment and prevention of recurrence of echinococcal liver disease are closed methods of echinococcectomy: a cyst pericystectomy, liver resection. When we use ultrasound resection techniques for closed (radical) surgical interventions, intra- and postoperative complications are reduced and the immediate and long-term results of patients with liver echinococcosis are improved.